Modern Manager and Requirements in the Innovative Economy - Pardaev, Olim (Indonesian Journal of Innovation Studies, 2019)
The article looks at the modern manager in the conditions of an innovative economy and its requirements. The requirements also include professional training of a manager, psychological qualities of a manager, general cultural level, and general academic level. The article provides a brief overview of the key aspects of the quality of a modern manager - his or her level of knowledge and the requirements for a modern manager.